COMFORTneo scale in preterm infants during live performed music therapy—Difference between close physical contact and hand touch contact - Kobus, Susann; Kleinbeck, Tim; Ader, Miriam; Dewan, Monia Vanessa; Dathe, Anne-Kathrin; Feddahi, Nadia; Felderhoff-Mueser, Ursula; Bruns, Nora (Frontiers in Neuroscience, 2024)
There is evidence that music therapy combined with physical contact to parents stabilizes the vital signs of hospitalized preterm infants. Yet, there is no evidence for the difference between simple contact by touching the infant in the incubator or cod, or close physical contact during music therapy sessions (MT). Behavioral effects of the various forms of attention toward the infant during therapy need to be elucidated. Our study aimed to quantify the effects of hand touch contact (HTC) and close physical contact (CPC) during live performed MT in preterm infants regardless of gestational age on behavioral state (assessed via COMFORTneo scale) and vital signs. A maximum of ten live music therapy sessions were delivered three to four times a week until hospital discharge to 50 stable infants. Pre-, during- and post-therapy heart rates, respiratory rates, oxygen saturations and COMFORTneo scores were recorded for each session. A total of 486 sessions was performed with 243 sessions using HTC and CPC each. The mean gestational age was 33 + 3 weeks, with 27 (54%) infants being male. We observed lower COMFORTneo scores, heart and respiratory rates and higher oxygen saturation during and after live performed music therapy independent of the kind of physical contact than before therapy. While pre-therapy values were better in the CPC group for all four variables, a higher mean response on COMFORTneo scale and vital signs was observed for HTC (COMFORTneo score −5.5, heart rate −12.4 beats per min., respiratory rate −8.9 breaths per min, oxygen saturation + 1.5%) compared to CPC (COMFORTneo score −4.6, heart rate −9.6 beats per min., respiratory rate −7.0 breaths per min, oxygen saturation + 1.1%). Nonetheless, post-therapy values were better for all four measures in the CPC group. Regression modeling with correction for individual responses within each patient also yielded attenuated effects of MT in the CPC group compared to HTC, likely caused by the improved pre-therapy values. Live performed music therapy benefits preterm infants’ vital signs and behavioral state. During CPC with a parent, the absolute therapeutic effect is attenuated but resulting post-therapy values are nonetheless better for both the COMFORTneo scale and vital signs.